Optimal AIN film deposition conditions for enhancing surface corrosion resistance and silver appearance - Sanguanmak, Pattarapol; Sakdanuphab, Rachsak; Sakulkalavek, Aparporn; Rudradawong, Chalermpol; Somjaijaroen, Natthawirot (My University, 2026)
This study investigates the development of AlN thin-film protective coatings for enhancing the corrosion resistance, surface hardness, and color stability of Ag 925 substrates used in decorative and wearable applications. AlN coatings were deposited by reactive DC magnetron sputtering, and the influences of working pressure and film thickness on bonding chemistry, oxygen incorporation, optical appearance, and artificial-sweat corrosion resistance were systematically evaluated. Increasing the working pressure promoted Al–O bond formation and noticeable surface discoloration, consistent with enhanced oxygen uptake that disrupted the near-surface Al–N bonding network. In contrast, films deposited within a moderate pressure window (2.5–7.5 × 10−1 Pa) exhibited minimal color change (ΔE < 3), maintained stable Al–N bonding characteristics, and achieved a hardness of approximately 5.2 GPa. Film thickness further governed the protective performance: ultrathin AlN layers provided only limited resistance, whereas coatings thicker than ~ 300 nm significantly improved surface resistance, as supported by the reduced chloride-induced discoloration (ΔE decreased from ~ 33.6 to ~ 11) and the effective suppression of Ag and Cu oxidation, as confirmed by FE-SEM/EDS analysis. These results demonstrate that both an optimal working pressure regime and a sufficiently thick coating (> 300 nm) are essential for achieving long-term color stability and corrosion resistance in wearable silver applications.